2003
DOI: 10.1002/polb.10481
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of liquids by electrically conductive immiscible polypropylene/thermoplastic polyurethane blends containing carbon black

Abstract: Immiscible polymer blends based on polypropylene/thermoplastic polyurethane (PP/TPU) are interesting host multiphase systems for the incorporation of low concentrations of conductive carbon black (CB) particles. The enhancement of conductivity (and the lower critical CB content for percolation) in the PP/TPU blend is achieved via double percolation, that is, structural and electrical. The CB particles form chainlike network structures within the TPU phase, which exhibit phase continuity of elongated particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 34 publications
0
47
2
Order By: Relevance
“…The ability to draw fibers from carbon black filled systems is very limited, while with nanotubes the processability is much better. Thus, it seems to be interesting also to investigate composites and blends based on CNTs for liquid sensing purposes.For melt-processed biphasic polymer/ CB composites, Narkis et al reported the liquid sensing behaviour of [30][31][32][33][34]. In the immiscible polymer blends containing CB, like PP/PA6/CB, HIPS/EVA/CB, and PP/TPU/CB, the liquid sensing behaviours depended on their components, composition, and composite morphologies, which could be influenced by the melt-processing method and mixing conditions.…”
mentioning
confidence: 99%
“…The ability to draw fibers from carbon black filled systems is very limited, while with nanotubes the processability is much better. Thus, it seems to be interesting also to investigate composites and blends based on CNTs for liquid sensing purposes.For melt-processed biphasic polymer/ CB composites, Narkis et al reported the liquid sensing behaviour of [30][31][32][33][34]. In the immiscible polymer blends containing CB, like PP/PA6/CB, HIPS/EVA/CB, and PP/TPU/CB, the liquid sensing behaviours depended on their components, composition, and composite morphologies, which could be influenced by the melt-processing method and mixing conditions.…”
mentioning
confidence: 99%
“…DC (direct current) electrical resistivity of these materials was found to be sensitive to benzene, n-heptane, methanol and methyl methacrylate [5]. Sensitivity to a mentioned liquids was also observed in a case of polymer blends of high impact polystyrene (as a matrix) and ethylene-co-vinyl acetate (as a dispersed phase) containing carbon black (electrically conductive filler) [6]. The filaments of thermoplastic polyurethane-carbon black compunds displayed an increase in resistance upon exposure to various alcohols (methanol, ethanol, and 1-propanol) [4].…”
Section: Introductionmentioning
confidence: 84%
“…A principle of operation these devices is based on a change of their electrical properties upon exposure to a studied sample. In a sensor technology both the intrisically conducting polymers (their conductivity can be changed by doping) and composites (electrically insulating polymer matrix with a conductive filler) are applied [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This makes it possible to detect the exposure to the external condition. For example, CPCs can be used for sensing mechanical stress [4,5], temperature [6], gas [7,8] vapor [9,10], pH and liquid [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%